Molecular Profiling Reveals Common and Specific Development Processes in Different Types of Gynecologic Cancers - Guo, Yuanli; Liu, Junfeng; Luo, Jiaqi; You, Xiaobin; Weng, Hui; Wang, Minyi; Ouyang, Ting; Li, Xiao; Liao, Xiaoming; Wang, Maocai; Lan, Zhaoji; Shi, Yujian; et al. (Frontiers in Oncology, 2020)
Background: Gynecologic cancers have become a major threat to women health. The molecular biology of gynecologic cancers is less understood as compared to breast cancer, and precision targeting is still in the cradle. Although being viewed collectively as a group of cancers within the female reproductive system, they are more often studied separately. A comprehensive within-group comparison on molecular profiles is lacking. Methods: We conducted a whole-exome sequencing study of cervical/endometrial/ovarian cancer samples from 209 Chinese patients. We combined our data with genomic and transcriptomic data from relevant TCGA cohorts to identify and verify common/exclusive molecular changes in cervical/endometrial/ovarian cancer. Results: We identified shared molecular features including a COSMIC signature of deficient mismatch repair (dMMR), four recurrent copy-number variation (CNV) events, extensive alterations in PI3K-Akt-mTOR signaling and cilium component genes; we also identified transcription factors and pathways that are exclusively altered in cervical/endometrial/ovarian cancer. The functions of the commonly/exclusively altered genomic circuits suggest 1) a common reprogramming process during early tumor initiation, which involves PI3K activation, defects in mismatch repair and cilium organization, as well as disruption in interferon signaling and immune recognition; 2) a cell-type specific program at later-stage of tumor development that eventually lead to tumor proliferation and migration. Conclusion: This study describes from a molecular point of view on how similar and how different are gynecologic cancers, and provides a hypothesis about the causes of the observed similarities and differences.